Integrated analysis of microbiome and metabolome reveals insights into cervical neoplasia aggravation in a Chinese cohort - Zhai, Qingzhi; Zhao, Luyang; Wang, Mingyang; Li, Li; Li, Li-an; Ye, Mingxia; Li, Mingxia; Xu, Chengfeng; Meng, Yuanguang (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCervical carcinoma (CC) remains one of the significant cancers threatening women's health globally. Increasing evidence suggests that alterations in the microbiota are closely associated with cancer development. However, the understanding of reliable biomarkers and underlying mechanisms during the aggravation of cervical neoplasia such as cervical intraepithelial neoplasia (CIN) and CC is still relatively limited.MethodsIn this study, cervical swab samples from 53 healthy controls, 51 high-grade squamous intraepithelial lesion (HSIL), and 52 CC patients were subjected to 16S rDNA sequencing and metabolomics analysis.ResultsWe observed significant differences in the cervical microbiota between CC patients and healthy controls or HSIL groups. Compared to the healthy controls, CC patients exhibited increased microbial diversity, decreased abundance of Lactobacillus, and notable changes in microbial composition. Metabolomics analysis revealed significantly elevated levels of the inflammatory mediator Prostaglandin E2 (PGE2) in CC samples. Through random forest modeling and ROC curve analysis, we identified a combination of key microbiota (Porphyromonas, Pseudofulvibacter) and metabolites (Cellopentaose, PGE2) as diagnostic biomarkers with high diagnostic value for CC. Furthermore, we found a significant correlation between the cervical microbiota Porphyromonas and the metabolite PGE2, suggesting a potential role of key microbiota in inducing inflammation.DiscussionThese findings indicate that alterations in cervical microbiota and metabolites may be closely associated with the occurrence and aggravation of cervical neoplasia, providing new insights for further understanding the mechanisms of cervical neoplasia progression and developing novel diagnostic markers and therapeutic approaches.